Investigating the role of "imagining in the story" from the point of view of Allameh Javadi Amoli - Mohammad Karami; Behroz Asadi (حکمت اسرا)
The main theme of this article is to examine the epitome (fantasy) in the story from the viewpoint of Allameh Javadi Amoli. Using the transcendent wisdom, he has provided a unique view of the authority in the story that has not yet been addressed independently. In this study, first, by referring to the numerous works of Allameh Javadi and the foundations of his epistemology and anthropology, the role of the epitome in the creation of human stories, the halt of human beings in the fantasy level, and the reasons for caution in dealing with non -argumentative stories were summarized from his point of view. And then in a descriptive-analytical manner; Explanatory and examined. The origin of the non -argumentative stories is nothing but a patent; This is the case with the composition of this power, so it also confuses Samin; The definite- though wise is potential- does not reach the present level of reason, while the true dignity of man is in the rule of reason and the obedience of authentic quotation. As a result, human beings are subject to fantasy, and human being subject to arguments, and with regard to the limitation of the capacity of talents, man must be the same, not Sami; Because Sami is busy with every story and story, but the supervision is subject to the reasoning and divine stories; Because the imagination is the creator of non -divine stories, but the Qur'anic theme is derived from the divine will and the honest, the truth